2020
DOI: 10.1186/s12974-020-01734-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Wnt7a in the role of M2c microglia in neural stem cell oligodendrogenesis

Abstract: Background: The participation of microglia in CNS development and homeostasis indicate that these cells are pivotal for the regeneration that occurs after demyelination. The clearance of myelin debris and the inflammatorydependent activation of local oligodendrocyte progenitor cells in a demyelinated lesion is dependent on the activation of M2c microglia, which display both phagocytic and healing functions. Emerging interest has been raised about the role of Wnt/β-catenin signaling in oligodendrogenesis and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…It is well known that activated microglia and infiltrating peripheral monocytes in CNS are crucial neuroinflammatory determinants in the pathophysiology of both MS and EAE. Together with primed T cells, they are the main inflammatory players involved in neuronal and oligodendrocyte alterations associated with synaptic dysfunction, subpial and axonal demyelination in MS/EAE (Mandolesi et al, 2015;Dong and Yong, 2019;Mecha et al, 2020). Increased microglial activity in brain regions involved in mood and cognitive control (including PFC and hippocampus) has been detected, by means of both PET and post-mortem clinical studies, in depressed MS patients in comparison to non-depressed MS patients and healthy controls (Politis, 2012).…”
Section: The Role Of Microglia In Ms Depressionmentioning
confidence: 99%
“…It is well known that activated microglia and infiltrating peripheral monocytes in CNS are crucial neuroinflammatory determinants in the pathophysiology of both MS and EAE. Together with primed T cells, they are the main inflammatory players involved in neuronal and oligodendrocyte alterations associated with synaptic dysfunction, subpial and axonal demyelination in MS/EAE (Mandolesi et al, 2015;Dong and Yong, 2019;Mecha et al, 2020). Increased microglial activity in brain regions involved in mood and cognitive control (including PFC and hippocampus) has been detected, by means of both PET and post-mortem clinical studies, in depressed MS patients in comparison to non-depressed MS patients and healthy controls (Politis, 2012).…”
Section: The Role Of Microglia In Ms Depressionmentioning
confidence: 99%
“…Inflammatory microglial necroptosis occurs, shutting down proinflammatory signals, and is followed by the repopulation of the lesion with regulatory microglia, a process required for efficient remyelination . Regulatory microglia can also promote SVZ-derived oligodendrogenesis and remyelination via Wnt7a production (Mecha et al, 2020).…”
Section: Roles Of Microglia In Remyelinationmentioning
confidence: 99%
“…Represented with similar function, NPCs secrete factors like TGF-β2 to transform MG into protective type [102], who in turn to support the maintenance and growth. The reparation on demyelination can also be initiated by M2 microglia, while through NSCs to bring about oligodendrogenesis and myelination [108]. Accumulating evidence has demonstrated that NSCs niches is the utmost region as the origin of the neural regenerative microenvironment, though its program of neurogenesis is a bit distinguished from the pattern after TBI.…”
Section: Nsc Might Integrate the Inflammatory Signal In Neural Regenementioning
confidence: 99%
“…Represented with similar function, NPCs secrete factors like TGF-β2 to transform MG into protective type 102 , who in turn to support the maintenance and growth. The reparation on demyelination can also be initiated by M2 microglia, while through NSCs to bring about oligodendrogenesis and myelination 108 .…”
Section: Communication Crosstalk and Integration In Neuroinflammatiomentioning
confidence: 99%